Mitigating SSR of Series-Compensated DFIG Wind Farms Based on Cascaded High-Gain State and Perturbation Observers - Xuelei Feng; Tianhao Wen; Xiaohan Liu; Yang Liu; Q. H. Wu (CSEE Journal of Power and Energy Systems)
This paper proposes a novel cascaded high-gain state and perturbation observer (CHGSPO)-based feedback linearization control (FLC) strategy for mitigating the sub-synchronous resonance (SSR) caused by the interactions between the series capacitor and doubly-fed induction generator-based wind farms (DFIGWFs). The CHGSPO is designed to estimate both the state and nonlinear perturbations of the series-compensated DFIGWF system. The nonlinear perturbation contains the disturbance originated from SSR, nonlinearities and uncertainties of the system model. The estimated state and perturbations are used by the FLC to eliminate the nonlinearities of the system and realize complete decoupling control of the DFIGWF. Additionally, the FLC effectively suppresses oscillatory signals detected by the CHGSPO. The proposed CHGSPO-based FLC exhibits remarkable robustness against uncertainties and external disturbances. The results of modal analysis and time domain simulations demonstrate the effectiveness of the proposed control strategy in SSR mitigation of the series-compensated DFIGWF system.